The Education of Playful Boys: Class Clowns in the Classroom - Barnett, Lynn A. (Frontiers in Psychology, 2018)
This longitudinal study identified degrees of playfulness in 278 kindergarten-aged children, and followed them through their next three school years to determine how playfulness was viewed by the children themselves, their classmates, and teachers. Perceptions of the social competence, disruptiveness, and labeling as the class clown, were assessed from all perspectives in each of first through third grades. Hierarchical linear modeling was conducted to account for the nesting of the data (children within classrooms within schools) and for the lack of independence between the measures. A central finding confirmed extant literature in that gender differences were dominant, with playful boys regarded as distinct from their less playful counterparts, while no such discrepancies appeared for girls. Playful boys were increasingly negatively regarded as rebellious and intrusive and were labeled as the “class clown” by their teachers. These findings were in direct contrast with children’s self-perceptions and those of their peers, who initially regarded more playful boys as appealing and engaging playmates. The data further revealed that the playful boys were stigmatized by their teachers, and this was communicated through verbal and nonverbal reprimands, and classmates assimilated this message and became increasingly denigrating of the playful quality in the boys. In stark contrast, girls’ playfulness levels were not a consideration in ratings by teachers or peers at any grade, nor did their classroom behaviors show significant variation. These negative perceptions were likely transferred by teachers to peers and to the children themselves, whereupon they changed their positive perceptions to be increasingly negative by third grade. The results contribute to the literature by demonstrating that playfulness in boys (but not girls) is often associated with the ‘class clown’ designation, and is viewed as an increasingly lethal characteristic in school classrooms, where compelling efforts are undertaken to discourage its expression and persistence.